Characterization of Plant Growth-Promoting Rhizobacteria (PGPR) Isolated from beach ridges interspersed with swales (BRIS) soil as potential biofertilizer - Zakiah Mustapha
The beneficial effects of plant growth promoting rhizobacteria (PGPR) on plant growth, yield and quality were consistently reported. PGPR were isolated around the world and demonstrated as biofertilizer. However, there are still very few studies have been conducted on the use oflocally isolated PGPR as biofertilizer especially from the Beach Ridges Interspersed with Swales (BRIS) soil. Therefore, this study aims to isolate and identify several strains of PGPR with multiple plant growth-promoting (PGP) characteristics from BRIS soil and determine their characteristic as biofertilizer. This is important as the locally isolated PGPR are more adaptable and might perform optimally in our environment and might have superior PGP characteristics as they are isolated from the problematic BRIS soil. A total of 24 bacterial isolates that have both abilities to fix-No and solubilize-P were successfully isolated from the rhizosphere of Acacia mangium at Apiary UniSZA. Based on their morphological and biochemical characteristics and the highest growth record in 5% molasses medium with 2% KN03, th-ee bacterial strains namely UA 1, UA 6 and UAA 2 identified as Burkholderia unamae, Bacillus amyloliquefaciens and Enterobacter asburiae respectively were selected for further studies. The three selected PGPR were further evaluated in single and mix strains for their PGP characteristics. The abilities to fix-N2, solubilize-P and K and produce IAA and siderophore were quantitatively determined. The effects of environmental factors (concentration of molasses medium and KN03, pH and temperature) were evaluated. Field trial on the effects of PGPR inoculations on Abelmoschus esculentus (okra) growth, physiology, yield and soil chemical contents wer also determin d. The three PGPR in single and in combination showed a high nitrogenase activities (17.00 - 21.63 nmol C2H4/mLIh), produce high soluble phosphate (32.00 - 54.38 ug/ml.), soluble potassium (11.55 - 17.45 ug/ml.), produce IAA (9.87 -17.30 ug/ml.) and produce siderophores unit (16.74 -46.74 %). Bacterial growth was optimum in 6% molasses medium, temperature 30°C and pH 6-7. These bacteria can also grow in high salinity of 8% KN03 in 6% molasses medium. Inoculation with single and mix bacterial strains on okra have significantly increased the leaves number and size, root dry weight, total dry biomass and okra's yield while reducing 30% ofNPK fertilizer. The soil available N, P and K, pH, CEC and total bacterial count were increased with bacterial inoculation. Combination of the isolated PGPR showed a better PGP characteristics and performance compared to the use of single strain. UA 1 and UA 6 have showed their own superior PGP characteristics and performance while UAA 2 was the weakest among the selected PGPR. UA 6 was more tolerance to high salinity, temperature and pH, produce the highest BNF rate and siderophores while UA 1 has solubilize the highest P and K and produced the highest lAA and okra yield. Thus, the isolated BRIS soil PGPR in this study either in single or mix form have shown significant multiple benefits of PGP characteristics and have potential to be used as biofertilizer.